Impact of metabolism and growth phase on the hydrogen isotopic composition of microbial fatty acids - Heinzelmann, Sandra M.; Villanueva, Laura; Sinke-Schoen, Danielle; Sinninghe Damsté, Jaap S.; Schouten, Stefan; van der Meer, Marcel T. J. (Frontiers in Microbiology, 2015)
Microorganisms are involved in all elemental cycles and therefore it is important to study their metabolism in the natural environment. A recent technique to investigate this is the hydrogen isotopic composition of microbial fatty acids, i.e. heterotrophic microorganisms produce fatty acids enriched in deuterium (D) while photoautotrophic and chemoautotrophic microorganisms produce fatty acids depleted in D compared to the water in the culture medium (growth water). However, the impact of factors other than metabolism have not been investigated. Here, we evaluate the impact of growth phase compared to metabolism on the hydrogen isotopic composition of fatty acids of different environmentally relevant microorganisms with heterotrophic, photoautotrophic and chemoautotrophic metabolisms. Fatty acids produced by heterotrophs are enriched in D compared to growth water with εlipid/water between 82 ‰ and 359 ‰ when grown on glucose or acetate, respectively. Photoautrophs (εlipid/water between -149 ‰ and -264 ‰) and chemoautotrophs (εlipid/water between -217 ‰ and -275 ‰) produce fatty acids depleted in D. Fatty acids become, in general, enriched by between 4 and 46 ‰ with growth phase which is minor compared to the influence of different metabolisms. Therefore, the D/H ratio of fatty acids is a promising tool to investigate community metabolism in nature.